Formulation and evaluation of stability o/w cream containing caffeine - Mohamad, Nor Hakimah; Ab. Hadi, Hazrina (2018)
INTRODUCTION: Cellulite or lipodystrophy is a major aesthetical concern among women who want to look beautiful. OBJECTIVES: The aim of this study was to evaluate the stability of topical slimming and anti-cellulite cream containing 2.5% of caffeine. METHODS: Formulation of oil-in-water cream containing 2.5% of caffeine and without caffeine (base) were prepared from mixing and homogenizing of three parts ingredients which are water bases ingredient, oil components and additional ingredients. Both creams were stored at different storage conditions of 40℃ ± 2℃ with 75% ± 5% relative humidity 30℃ ± 2℃ with 75% ± 5% relative humidity for 12 weeks to predict their stability. During storage, the formulation and base were evaluated for physical analysis (appearance, homogeneity, colour, and odour), pH, centrifugation, rheology property, zeta potential, and size of particle in different time intervals (day 0, 2nd, 4th, 8th and 12th weeks). The microbial test was conducted to ensure the formulation free from any microbes. RESULTS: Experimental findings showed that both creams (base and formulation) maintained their physical observations by showing yellow whitish creamy, homogenous appearance and pleasant odour with no phase separation after centrifugation throughout entire period of study. Besides, both creams remained exhibited a non-Newtonian fluid behaviour and good microbial stability during 12 weeks. There were significant changes (p<0.05) in droplet size, pH and zeta potentials values of creams during 12 weeks of storage but they still remained in acceptable ranges to be considered a stable emulsion. CONCLUSION: The results indicated that the prepared cream containing 2.5% of caffeine was stable over the period of the study.